The Influence of School Facilities and Educational Cost on Students Decision Making to Continue Education to Senior High School Al Ulum Terpadu with the School Location as Moderating Variable - Andrew Satria Lubis (International Conference of ASEAN Prespective and Policy (ICAP), 2018)
Every educational institution wants to have quality school facilities and reasonable educational cost to attract students interest to continue their education to a higher educational institution. To gain the number of students. Based on governments regulations, an educatinal institution must be able to optimize the supporting factors of the students decision making. One of the factors that can uphold the students decision to continue their education is the extent that the school facilities are available and organized and the educational cost is reachable. The present research uses 55 tenth grade students of SENIOR HIGH SCHOOL Al Ulum Terpadu as subjects. The purpose of the research is to find out and to analyse the influence of the school and educational cost on the students decision making in order to continue their educational to SENIOR HIGH SCHOOL Al Ulum Terpadu with the school location as a moderating variable. The research is Descriptive-Quantitative and descriptive explanatory. The data are collected by means of interview documentation and survey by distributing the questionnarie to the 55 tenth grade students of SENIOR HIGH SCHOOL Al Ulum Terpadu with full sampling technique. Data analysis technique applied is multiple liniear regression using SPPS Software. The result of the first model shows that school facilities and educational cost simultaneously have positive and significant influence on the students decision making to continue their education to SENIOR HIGH SCHOOL Al Ulum Terpadu. Partially school facilities has positive and significant influence on the students decision making where the educational cost has negative and significant on the students decision making to continue their education to SENIOR HIGH SCHOOL Al Ulum Terpadu. The result of the second model shows that the school location can moderate the influence of the educational cost on the students decision making. On the other hand the school location cannot moderate the influence of school facilities on the students decision making.